Effectiveness of Additional Employee Income Policy at the Central Sulawesi Provincial DPRD Secretariat - Rudin M.; Maria Lea Frensy Bakarbessy (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The study examines the effectiveness of employee income allowances at the Secretariat of the Regional People’s Representative Council of Central Sulawesi Province, addressing a research gap where prior studies mainly focused on technical budget distribution without linking it to performance in legislative institutions. This study aims to at evaluating this policy within a holistic framework covering budget realization, employee performance, and Civil Servants’ behavioral responses it applies a qualitative descriptive method using observations, interviews with six key informants, and document analysis. Effectiveness was measured by comparing budget realization and plans in line with the Decree of the Minister of Home Affairs Number 690,900,327 of 1996. Findings indicate that from 2021 to 2024, budget realization consistently exceeded 100%, demonstrating strong administrative alignment between planning and employee needs. However, this fiscal efficiency did not fully translate into improved performance quality due to challenges such as inadequate performance appraisal mechanisms, limited technology, and weak supervision. The study concludes that allowance effectiveness depends not only on budget absorption but also on integrated evaluation systems, adaptive leadership, and sufficient supporting infrastructure.